Morphinan alkaloids from the leaves of alphonsea cylindrica and their antibacterial properties - Mohd Azlan Nafiah (Tanjung Malim, 2023)
Morphinan alkaloids from the leaves of alphonsea cylindrica and their antibacterial properties by Mohd Azlan Nafiah